BANKERS’ ATTITUDES TO THE LEGAL POSITION OF BANK INTEREST: NEW INSIGHTS FOR THE DEVELOPMENT OF FIQH WASATIYAH MALIYAH - Ahmad Dakhoir; Jefry Tarantang; Ghozali Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
This study explains the phenomena of certain Indonesian bankers’ fear regarding bank interest. This anxiety led bankers both of conventional and sharia to extreme attitudes such as the decision of employees to stop working or move to work in Islamic banks, assuming that his position is correct and considers conventional bankers to be illegitimate work. These two understandings and attitudes underlie the authors interested in analyzing and discovering how to build a tolerant and moderate fiqh concept in the world of Islamic banking and finance. This research uses a type of qualitative-descriptive research, with a prophetic approach and fiqh tolerance approach or fiqh wasatiyah in the field of Islamic banking and finance. The theory of maqasid al-sharia al-iqtishadiyyah is used as the ground theory of this paper. The results of this research show that: first, the anxiety of conventional bank employees is caused by factor of understanding and interpretation that bank that uses the interest system is usury system and usury is illegal. Second, that understanding and attitude of extremism can be seen as stopping work suddenly, disappearing without any reason, changing how to dress, easily forbidding something, and finally stop working in conventional banks